A self-sustained soft actuator able to rock and roll. Issue 74 (27th August 2019) - Pilz da Cunha, Marina; Peeketi, Akhil R.; Mehta, Kanishk; Broer, Dirk J.; Annabattula, Ratna K.; Schenning, Albert P. H. J.; Debije, Michael G.
Abstract : Liquid crystalline networks of specific geometry are observed to undergo thermally triggered chaotic continual rocking motion and light triggered rolling. Abstract : A triangular shaped liquid crystal network is shown to undergo a continual, rocking chair-like oscillatory chaotic motion upon exposure to a surface of constant temperature. With the addition of an azobenzene chromophore, dual response is achieved, extending the actuation freedom towards a film that shows rocking and rolling motion.